2009
DOI: 10.1093/cvr/cvp312
|View full text |Cite
|
Sign up to set email alerts
|

S1P3-mediated cardiac fibrosis in sphingosine kinase 1 transgenic mice involves reactive oxygen species

Abstract: These results suggest that chronic activation of SPHK1-S1P signalling results in both pathological cardiac remodelling through ROS mediated by S1P3 and favourable cardioprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 30 publications
(48 reference statements)
6
107
0
Order By: Relevance
“…In contrast, mice with germ line ablation of the Sgpp1 gene, which encodes the degrading enzyme S1P phosphatase 1 (Allende et al, 2013) and mice with forced over-expression SphK1 via an Sphk1 transgene driven by a broad spectrum promoter (Takuwa et al, 2010) do not have differences in circulating S1P (plasma) as compared with wildtype control mice. However, mice lacking the S1P-degrading enzyme S1P lyase (via germ line ablation of Sgpl1) have serum S1P levels that are 4-fold higher than wild-type littermates (Bektas et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, mice with germ line ablation of the Sgpp1 gene, which encodes the degrading enzyme S1P phosphatase 1 (Allende et al, 2013) and mice with forced over-expression SphK1 via an Sphk1 transgene driven by a broad spectrum promoter (Takuwa et al, 2010) do not have differences in circulating S1P (plasma) as compared with wildtype control mice. However, mice lacking the S1P-degrading enzyme S1P lyase (via germ line ablation of Sgpl1) have serum S1P levels that are 4-fold higher than wild-type littermates (Bektas et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In physiologic conditions, MABP was not altered by the loss of Sphk1 2/2 or Sphk2 2/2 (Furuya et al, 2013;Gorshkova et al, 2013), or the overexpression of SPHK1 (Takuwa et al, 2010). In a model of histamine-induced hypotension, Olivera et al (2010) showed that Sphk1 2/2 mice, but not Sphk2 2/2 mice, were significantly more hypotensive than WT mice.…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 93%
“…A clear role for S1P 3 has also been demonstrated in the regulation of heart rate in rodents (Forrest et al, 2004;Sanna et al, 2004), and it has been shown to regulate lymphoid endothelial cells (Girkontaite et al, 2004) and to have effects on endothelial progenitor cells (Walter et al, 2007). S1P 3 regulates myocardial perfusion and provides protection in ischemia-reperfusion injury (Levkau et al, 2004;Theilmeier et al, 2006;Means et al, 2007) and further influences vasorelaxation (Nofer et al, 2004) and cardiac fibrosis (Takuwa et al, 2009). Other influences on myofibroblasts (Keller et al, 2007), as well as S1P 3 links to PAR-1 signaling that couples coagulation events with inflammation (Niessen et al, 2008), have been reported.…”
Section: B Sphingosine 1-phosphate Receptorsmentioning
confidence: 99%